Computed tomography features and clinicopathological characteristics of resectable esophageal sarcomatoid carcinoma: a retrospective study - Li, Meng; Li, Yang; Wang, Mingbo; Deng, Huiyan; Wang, Xiangming; Shi, Gaofeng; Zhang, Andu; Ren, Jialiang (Frontiers in Oncology, 2025)
ObjectivesEsophageal sarcomatoid carcinoma (ESC) is a rare malignant tumor. This study aims to analyze the computed tomography (CT) features and clinicopathological characteristics of resectable ESC.MethodsThe CT and clinicopathological data of 25 patients with ESC, confirmed by postoperative pathology, were retrospectively analyzed. The preoperative CT feature analysis included the average tumor CT attenuation value (CTTumor), the average normal esophagus CT attenuation value (CTNormal), the tumor-to-normal esophagus attenuation ratio (TNR), enhancement pattern, tumor margin, and tumor morphology, which was classified into two types: mass-forming type and wall-thickening type. Additionally, CT-measured tumor thickness (cTT), CT-measured tumor length (cTL), and CT-measured tumor volume (cTV) were measured and recorded. The analysis of clinicopathological characteristics encompassed variables such as age, gender, clinical symptoms, pathological tumor thickness (pTT), pathological tumor length (pTL), T stage, N stage, lymphovascular invasion status, and neural invasion status. To assess the agreement and correlation between CT features and pathological results, Bland-Altman plots and Pearson correlation coefficient analyses were performed for pTT versus cTT and pTL versus cTL, respectively.ResultsAmong the 25 patients with ESC, 19 were male and 6 were female. The patients’ ages ranged from 47 to 73 years, with a mean age of 65.48 ± 6.85 years and a median age of 68 years. The pathological staging results showed that 14 cases were at stage T1, 5 cases at stage T2, 5 cases at stage T3, and 1 case at stage T4. Lymph node metastasis was identified in 12 cases, including 5 classified as N1, 4 as N2, and 3 as N3. The pTT ranged from 0.50 to 4.00 cm, with a mean of 1.92 ± 1.02 cm and a median of 1.50 cm; the cTT ranged from 0.60 to 4.10 cm, with a mean of 2.02 ± 0.90 cm and a median of 1.66 cm. Bland-Altman analysis demonstrated a mean difference of 0.10 cm between cTT and pTT, with 92.0% (23/25) of cases lying within the 95% limits of agreement (Mean ± 1.96 SD). The Pearson correlation coefficient between the two measurements was 0.980, indicating a strong positive correlation. The pTL ranged from 2.00 to 7.00 cm, with a mean of 4.24 ± 1.50 cm and a median of 4.00 cm; the cTL ranged from 2.57 to 7.50 cm, with a mean of 4.41 ± 1.48 cm and a median of 4.16 cm. Bland-Altman analysis demonstrated a mean difference of 0.18 cm between cTL and pTL, with 92.0% (23/25) of cases lying within the 95% limits of agreement. The Pearson correlation coefficient was 0.884. The cTV ranged from 1.56 cm³ to 41.49 cm³, with a median of 8.25 cm³. Regarding tumor morphology, 20 cases presented as mass-forming type, while 5 were classified as wall-thickening type. Significant differences in both pTT and cTT were observed between the two morphological types; however, no statistically significant differences were found in other CT features.ConclusionESC is a rare malignant tumor characterized by distinctive CT features. The majority of cases manifest as the mass-forming type, while a smaller proportion present as the wall-thickening type. The definitive diagnosis of ESC depends on pathological examination.